Circular - Roberts, Wilfrid
010-0028-001 17th December, 1936. Dear Sir, (or Madam), I write to remind you that the meeting held on the 16th December in the House of Commons of organisations engaged in relief work in Spain was adjourned until 4 p.m. on Monday, 21st December, at Friends House, Euston Road. For your information, I would remind you that the meeting at the House of Commons passed a resolution that the British Government should be called upon to facilitate the evacuation of the civil population, especially women and children, from Madrid by international action through the League of Nations; and to offer substantial help for this purpose. On the question of organisation for future work, I suggest that more progress will be made on Monday if we approach the problem from the point of view of what requires to be done in Spain, and devise, if necessary, some further co-ordinating organisation to carry out the collection of funds and their administration to meet the needs of the situation. To this end I am asking each individual society to supply a short report as to what the present scope of their work is, what funds they have to carry it out, and what larger work they could undertake. I trust that your society will be represented at the meeting on Monday. Yours sincerely, WILFRID ROBERTS. 292/946/10/30